Optimalisasi Active Learning Sebagai Strategi Meningkatkan Motivasi Dan Hasil Belajar Di Era Industri 4.0 - M. Fadlan Choiri; Neviyarni; Herman Nirwana (CV. ITTC INDONESIA, 2025)
The Industrial Revolution 4.0 has brought significant changes to the field of education, demanding innovative and relevant learning approaches. This study examines the optimization of Active Learning as an effective teaching strategy to enhance students' motivation and learning outcomes in the digital era. Through a literature review, the study finds that Active Learning facilitates students' direct involvement in the learning process, developing critical, analytical, and collaborative thinking skills. Methods such as brainstorming, group discussions, and the utilization of web-based technologies have proven to improve learning quality. This study concludes that implementing Active Learning, supported by proper planning, appropriate technique selection, and the use of interactive technologies, can create meaningful, engaging, and adaptive learning experiences to address the challenges of the Industrial Revolution 4.0.